Cancer Communication Outside of the Physician-Patient Relationship: The Experience of Communicating and Understanding the Meaning of Prognosis. (August 2019) - Adamson, Matthew; Cotoc, Crina; Choi, Kelsey; Notaro, Stephen
Research Question: How does the process of engagement and integration of sources of information outside patient–physician interaction affect how individuals with cancer interpret their treatment experience and prognosis? Background: Studies of patient–physician communication of prognosis in oncology highlight areas where misunderstanding occurs: understanding consequences of treatment, likelihood of treatment success, probability of cure, status/progression of illness, and prognosis. Theories proposing mechanisms that underlie this discrepancy cannot account for all instances of misunderstanding, including when complete and direct physician disclosure occurs. Prior research focused on patient–physician communication event(s) and immediate antecedents and consequences. However, less is known about what happens to information once it has been communicated and how a patient's process to interpret the meaning of their experience affects their understanding of it. Our study explores this question by examining patient communication with sources of information other than treating physicians. Methodology: We conducted 10 semi-structured qualitative interviews with individuals diagnosed with 4 types of cancer at different stages. The interviews were analyzed using inductive qualitative analysis. Results: Participants in our sample consulted a variety of additional sources to give context and understanding to their communicated prognosis. These were important contributors to how they understood their prognosis and incorporated that understanding. They included family, friends/acquaintances, cancer survivors, support/survivor groups, secondary health-care staff, and relevant informational materials. Different motivations for seeking out these sources were also expressed. Participants expressed a link between their understanding of their prognosis and the variety of outside sources they enlisted for input and support.